Self-assembled multilayers of polyethylenimine and DNA: Spectrophotometric and electrochemical characterization and application for the determination of acridine orange interaction - Ferreyra, Nancy Fabiana (2009)
This work deals with the study of the interaction between acridine orange (AO) and calf-thymus double stranded DNA (dsDNA) present in supramolecular architectures built on gold electrodes modified with mercapto-1-propanesulfonic acid (MPS) by self-assembling of polyethylenimine and dsDNA. The optimal conditions for building the supramolecular architecture were obtained from UV-vis spectrophotometric experiments. The electrochemical studies were performed by adsorptive transfer square wave voltammetry from the evaluation of the oxidation signal of AO accumulated within the multistructure. The effect of the number of PEI-dsDNA bilayers (Au/MPS/(PEI-dsDNA)n) on the accumulation and electrooxidation of AO is also discussed.